First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The Relationship Between Humans and Capuchins (Sapajus sp.) in an Urban Green Area in Brazil - Adriane Suzin; Janaína P. Back; Michel V. Garey; Lucas M. Aguiar (International Journal of Primatology, 2017)

Structure–Function Relationships of Four Stereoisomers of a Brassinolide Mimetic on Hypocotyl and Root Elongation of the Brassinosteroid-Deficient det2-1 Mutant of Arabidopsis - Leonid V. Kurepin; Michael A. Bey; Thomas G. Back; Richard P. Pharis (Journal of Plant Growth Regulation, 2016)

Interaction of Brassinosteroids with Light Quality and Plant Hormones in Regulating Shoot Growth of Young Sunflower and Arabidopsis Seedlings - Leonid V. Kurepin; Se-Hwan Joo; Seong-Ki Kim; Richard P. Pharis; Thomas G. Back (Journal of Plant Growth Regulation, 2012)

Growth and carbon stock change in eucalypt woodlands in northeast Australia: ecological and greenhouse sink implications - W. H. Burrows; B. K. Henry; P. V. Back; M. B. Hoffmann; L. J. Tait; E. R. Anderson; N. Menke; T. Danaher; J. O. Carter; G. M . McKeon (Global Change Biology, 2002)
Data from 57 permanent monitoring sites are used to document the growth in woody vegetation and estimate the carbon sink in 27 M ha of eucalypt woodlands (savannas), contained within c. 60 M ha of grazed woodlands in Queensland (northeast Australia). The study sites are shown to be representative of the environment and structure of the eucalypt woodlands in the defined study area. Mean basal area increment for all live woody plants in 30 long‐term sites, with an average initial basal area of 11.86 ± 1.38 (SE) m 2 ha −1 , was 1.06 m 2 ha −1 over a mean 14 years timeframe. The majority of the measurement period, commencing between 1982 and 1988, was characterized by below‐average rainfall. The increase in live tree basal area was due primarily to growth of existing trees (3.12 m 2 ha −1 ) rather than establishment of new plants (0.25 m 2 ha −1 ) and was partly offset by death (2.31 m 2 ha −1 ). A simple but robust relationship between stand basal area and stand biomass of all woody species was developed for the eucalypt dominant woodlands. Analysis of above‐ground carbon stocks in live and standing dead woody plants gave a mean net above‐ground annual carbon increment for all 57 sites of 0.53 t C ha −1 y −1 , similar to values estimated elsewhere in world savannas. Published root : shoot ratios were used to infer C flux in woody root systems on these sites. This results in an estimated sink in above‐ and below‐ground biomass of 18 Mt C y −1 over the eucalypt woodlands studied, and potentially up to 35 Mt C y −1 if extended to all grazed woodlands in Queensland. It is suggested that introduction of livestock grazing and altered fire regimes have triggered the change in tree‐grass dominance in these woodlands. Thus, change in carbon stocks in the grazed woodlands of Queensland is identified as an important component of human‐induced greenhouse gas flux in Australia, equivalent in magnitude to c . 25% of the most recently published (1999) total estimated national net emissions. The latter inventory takes into account emissions from land clearing, but does not include the sink identified in the present study. This sequestration also represents a small but significant contribution to the global terrestrial carbon sink.